Made to Order : Painted Ceramics of Ancient Teotihuacan - Conides, Cynthia (University of Oklahoma Press, 2018)
Made to Order, the first systematic study of more than 150 painted portable artworks produced in Teotihuacan, offers a unique, deeply informed perspective on the cultural practices and artistic techniques of the largest urban community in pre-Hispanic Mesoamerica